Appraisal of combined technical and financial packages for major civil engineering works - Ng, Heng Hoong. (2009)
Given the increasingly widespread perception among international engineering & construction companies that the ability to offer financing packages will enhance their chances of winning contracts, there is a corresponding need on the part of the project sponsors to be able to evaluate these financing packages which are often complex.